Development and Validation of a Web Server-Based Internet of Things (IoT) Trainer for Practical Learning in Higher Education - Zainuddin Zainuddin; Bakhran A. Rauf; Abdul Muis Mappalotteng (Jurnal Teknologi Pendidikan, 2026)
The rapid advancement of Internet of Things (IoT) technology has significantly influenced engineering and computer technology education, particularly in laboratory-based practical learning. However, many higher education institutions still face limitations in providing integrated IoT laboratory facilities, causing learning to rely on simulations or fragmented hardware modules that do not adequately represent real-world IoT system integration. This study aims to develop and validate a web server-based IoT trainer to support practical learning in higher education. The research employed a Research and Development (R&D) approach consisting of six stages: needs analysis, prototype design, product development, expert validation and limited trials, product revision, and dissemination. The developed trainer integrates an ESP32 microcontroller with multiple sensors and actuators, enabling real-time monitoring and control through an embedded web server. Data were collected through functional testing, system performance testing, and expert validation involving six experts in media, content, and instructional design. Data analysis used descriptive statistics and percentage-based feasibility calculations. The results indicate that all hardware components operated with error rates below 5% and response times under 250 ms. The web server system achieved an average response time of 648.1 ms with an error rate of 0%, indicating high reliability. Expert validation showed very high feasibility across all aspects, including programming (99.2%), content relevance (98.8%), and instructional design (100%). These findings demonstrate that the developed IoT trainer is technically reliable, pedagogically appropriate, and suitable for supporting IoT practical learning in higher education.